Preparedness for and impact of COVID-19 on primary health care delivery in urban and rural Malawi: a mixed methods study - Tracy Morse; Kondwani Chidziwisano; Gift Kawalazira; Mackwellings Maganizo Phiri; Eleanor Elizabeth MacPherson; Mindy Panulo; Khumbo Kalua; Chawanangwa Mahebere Chirambo; Zaziwe Gundah; Penjani Chunda (BMJ Open)
Objective Across Africa, the impact of COVID-19 continues to be acutely felt. This includes Malawi, where a key component of health service delivery to mitigate against COVID-19 are the primary healthcare facilities, strategically placed throughout districts to offer primary and maternal healthcare. These facilities have limited infrastructure and capacity but are the most accessible and play a crucial role in responding to the COVID-19 pandemic. This study assessed health facility preparedness for COVID-19 and the impact of the pandemic on health service delivery and frontline workers.Setting Primary and maternal healthcare in Blantyre District, Malawi.Participants We conducted regular visits to 31 healthcare facilities and a series of telephone-based qualitative interviews with frontline workers (n=81 with 38 participants) between August 2020 and May 2021.Results Despite significant financial and infrastructural constraints, health centres continued to remain open. The majority of frontline health workers received training and access to preventative COVID-19 materials. Nevertheless, we found disruptions to key services and a reduction in clients attending facilities. Key barriers to implementing COVID-19 prevention measures included periodic shortages of resources (soap, hand sanitiser, water, masks and staff). Frontline workers reported challenges in managing physical distancing and in handling suspected COVID-19 cases. We found discrepancies between reported behaviour and practice, particularly with consistent use of masks, despite being provided. Frontline workers felt COVID-19 had negatively impacted their lives. They experienced fatigue and stress due to heavy workloads, stigma in the community and worries about becoming infected with and transmitting COVID-19.Conclusion Resource (human and material) inadequacy shaped the health facility capacity for support and response to COVID-19, and frontline workers may require psychosocial support to manage the impacts of the COVID-19 pandemic.